The Study on 19 Learning Activities of The Sixth-Grade Secondary School Students - Shagjjav, Ichinkhorloo; Narantsetseg, Munkhtsetseg (Lavai - International Journal of Education, 2022)
The study aims to illuminate the level of the learning abilities of the 6th grade secondary schools students. A total of 1026 sixth-grade students from 13 secondary schools of Ulaanbaatar (the capital city), Selenge, Khentii, and Tuv Provinces participated in this study. The questionnaire was focused on assessing students' lerning skills and evaluate their learning abilities by 19 activities. To collect data, the questionnaire was designed with a five-point Likert scale consisting of 1 (“not at all”), 2 (“a little bit”), 3 (“sometimes”), 4 (“often”), and 5 (“always”). The participants consisted of 452 male students (44.1%) and 574 female students (55.9%), whereas 744 students (72.5%) were from schools of the capital city and 282 students (27.5%) from schools of rural areas. To analyze the validity factors and the study reliability, the SPSS Version 23 statistical program was used for data analysis and such research methods as the descriptive statistics and t-tests were applied. The study results demonstrate that students do their homework without any help (M=4.38) and listen to others (M=4.36). This illustrates that the students' self-learning skills show higher mean score. On the other hand, the mean score of the students' learning ability of making notes about the general idea of books they read (M=3.09) and getting some help from others (M=3.26) show the least mean score. This reveals that students do not do such activities at all. The study concludes that 87.16% of total 1026 students can conduct 19 active learning activities whereas 12.84% of students do not do such activities. Ерөнхий боловсролын сургуулийн VI ангийн сурагчдын сурах ерөнхий 19 үйлийн судалгаа, үр дүн Хураангуй: Энэхүү судалгаа нь ЕБС-ийн VI ангийн сурагчдын сурах ерөнхий үйлийн төлөв байдлыг илрүүлж тогтоох зорилготой. Тухайлбал, сурагчийн 1/ном уншихтай холбоотой 4 үйл: уншсан эхээс хэрэгтэй зүйл олж авах, уншсан номын утгыг өөрийн үгээр ярих, номын утгыг эргэцүүлэн бодох, уншсан зүйлийг тэмдэглэх, 2/ ярих үйл: сурагч санаа бодлоо бусдад ойлгомжтой ярих, 3/ сонсох 3 үйл: бусдын яриаг анхааралтай сонсох, бусдын ярианы гол санааг олох, сонссон зүйлд дүгнэлт хийх, 4/ асуулт асуух үйл, 5/ бүтээлч шинжтэй 2 үйл: шинэ санаа дэвшүүлэх, үгийн утгыг өөрийн үгээр тайлбарлах, 6/ хичээл дээр олж мэдсэн зүйлээ өөрийн амьдралд хэрэглэх, 7/ мэдлэг чадвараа хянах 2 үйл: юу шинээр мэдэж авснаа ойлгох, мэдлэг чадварт нь ямар алдаа байгааг олох, 8/ бие даах чадвар, 9/ төлөвшил, хандлагатай холбоотой 4 үйл: бусдад тусалдаг, бусдаас тусламж авдаг, зан байдал, харилцаанд нь байгаа сайн болон болохгүй зүйлийг олох зэрэг ерөнхий үйлийн судалгааг хийснээрээ шинэлэг болно. Судалгааны зарим үр дүн нь сурагчид гэрийн даалгавар, дасгал хийхдээ бие даан хийж чаддаг (M=4.38), багшийн болон бусдын яриаг анхааралтай сонсож чаддаг (M=4.36) болох нь харагдаж байна. Харин уншсан номын утга, санаа, үг зэргийг бичиж авах байдал (M=3.09), суралцах явцад бусад сурагчдаас тусламж авах (M=3.26) үйлийн дундаж үзүүлэлт хамгийн бага ба дээрх үйлийг төдийлөн хийдэггүй болохыг харж байна. Түлхүүр үг: Эх, санаа бодол, асуулт тавих, хянах, бие даан хийх